2014
DOI: 10.1002/cncr.28577
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of individuals with breast cancer rearrangements in BRCA1 and BRCA2

Abstract: ; and the Northwestern Cancer Genetics Group BACKGROUND: Large rearrangements in BRCA1 and BRCA2 occur in a small percentage (< 1%) of patients tested for hereditary breast (BC) and ovarian cancer. It is unclear what factors predict BRACAnalysis Large Rearrangement Test (BART) positivity. METH-ODS: Data from 6 centers were included in this analysis. Individuals with negative Comprehensive BRACAnalysis tested for BART were included. RESULTS: From 1300 individuals, 42 (3.2%) were BART positivity. Factors positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…They are more likely to be identified with copy number assays, or whole exome and whole genome approaches, now more commonly applied. Jackson et al reported rearrangements in 42 of 1300 (3.2%) patients referred for BRCA mutation testing and only 10 of the 42 had met Myriad criteria [ 34 ]. Our patient’s outcome of an over 5-year olaparib-maintained CR identifies her as an exceptional responder, remarkable even for patients with BRCA mutation-associated breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They are more likely to be identified with copy number assays, or whole exome and whole genome approaches, now more commonly applied. Jackson et al reported rearrangements in 42 of 1300 (3.2%) patients referred for BRCA mutation testing and only 10 of the 42 had met Myriad criteria [ 34 ]. Our patient’s outcome of an over 5-year olaparib-maintained CR identifies her as an exceptional responder, remarkable even for patients with BRCA mutation-associated breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of mutations found to date in the BRCA1/BRCA2 genes in breast and/or ovarian cancer families are point mutations or small insertions and deletions scattered over the coding sequence and splice junctions. Large rearrangements in BRCA1 and BRCA2 occur in a small percentage (<1%) of patients tested for hereditary breast and ovarian cancer [ 15 ]. Moreover, the mutation was detected in a male patient.…”
mentioning
confidence: 99%
“…To the best of our knowledge, the majority of mutations of the BRCA1/BRCA2genes in breast and/or ovarian cancer families are point mutations or small insertions and deletions spread over the coding sequence and splice site junctions. It is noteworthy that large rearrangements in BRCA1and BRCA2 accounted for less than 1% of evaluated patients suffering from hereditary breast and ovarian cancer [21]. All of these mutations are capable of shortening BRCA1 protein, leading to failing to its physiologic function [9].…”
Section: High-penetrant Genementioning
confidence: 99%